Dose of NPK phonska fertilizer in baby corn sweet corn (Zea mays saccharata Strut) plants to entisol - Sukmawati, Sukmawati; Busaifi, Riski; Suriadi, Ahmad; Ranggaini, Magfirahti; Komariah, Komariah (Universitas Muhammadiyah Mataram, 2024)
Baby corn sweet corn is a type of vegetable that has high potential to be developed. Baby corn sweet corn is popular and desirable and can grow and produce optimally on all types of soil. Sweet baby corn productivity must be continuously improved by maintaining soil fertility and using superior varieties. Maintaining soil fertility by fertilizing is a priority activity in sweet baby corn cultivation. The recommended fertilizer to be added in sweet baby corn cultivation is NPK Phonska fertilizer. This study was conducted with the aim to determine the effect of various doses of NPK Phonska fertilizer on the yield of sweet corn baby corn (Zea mays Saccharata Sturt) on Entisol soil. The research was carried out in the Experimental Garden of the Faculty of Agriculture, Nahdlatul Wathan University Mataram in Perampuan Village which was carried out within a period of 3 months. The design used in this study is a completely randomized design (CRD) using one treatment, namely the treatment of NPK phonska fertilizer dose (P) with five treatment levels, namely: P0, P1, P2, P3 and P4. Each treatment was multiplied 3 times and made serial plants so that each experimental unit would consist of 2 plant samples. The number of polybag pots in this study was 30 polybag pots. The results illustrated that the highest sweet baby corn yield parameters were found at the treatment level with a dose of 200 kg/ha NPK phonska fertilizer. The application of NPK phonska fertilizer 200 kg/ha can increase the cob length and cob diameter of sweet baby corn both with and without cob.